HYPER PRESIDENTIALISM AND FIRST YEAR OF THE TURKISH TYPE OF PRESIDENTIALISM - Korbayram, Azam; Ekinci, Ahmet (International Scientific Journal Vision, 2022)
The new government system of Turkey can be described as hyper-presidentialism, this is because the president then becomes the arbiter of all powers. In another word, the power to enact decrees, appoint bureaucrats and judicial officials into offices, and the power to dissolve a parliament belongs solely to the president. As strong presidency fuse with disciplined party system as well as concurrent elections and 10 percent electoral threshold, the president possibly poses a great danger to the separation of powers. Additionally, with regards to the presidential term, the president constitutionally holds the power to be elected only for two terms in Turkey. However, Erdoğan and his supporters believe that the 2017 constitutional amendments that changed the system of government has reset the agenda. Thus, the 2017 amendments offered Erdoğan a secret opportunity to join the presidential election race for a third, and even a fourth term.